2005
DOI: 10.1021/jm0505011
|View full text |Cite
|
Sign up to set email alerts
|

Toward Selective Histone Deacetylase Inhibitor Design:  Homology Modeling, Docking Studies, and Molecular Dynamics Simulations of Human Class I Histone Deacetylases

Abstract: Histone deacetylases (HDACs) play an important role in gene transcription. Inhibitors of HDACs induce cell differentiation and suppress cell proliferation in tumor cells. Although many HDAC inhibitors have been designed and synthesized, selective inhibition for class I HDAC isoforms is a goal that has yet to be achieved. To understand the difference between class I HDAC isoforms that could be exploited for the design of isoform-specific HDAC inhibitors, we have built three-dimensional models of four class I hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
195
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(205 citation statements)
references
References 38 publications
10
195
0
Order By: Relevance
“…Development of inhibitors with selective isoenzyme specificities seems to be feasible on the level of enzyme inhibition (15,(47)(48)(49) and HDAC protein degradation (50). The genetically defined model expressing a mutant protein that is inactive and does not integrate into multiprotein complexes (e.g., corepressor) corresponds closely to drug-induced degradation of HDAC2 but not fully to inhibition of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Development of inhibitors with selective isoenzyme specificities seems to be feasible on the level of enzyme inhibition (15,(47)(48)(49) and HDAC protein degradation (50). The genetically defined model expressing a mutant protein that is inactive and does not integrate into multiprotein complexes (e.g., corepressor) corresponds closely to drug-induced degradation of HDAC2 but not fully to inhibition of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…2A). These correspond to Cys 261 and Cys 273 residues of HDAC1, which appear to be surface-accessible, according to homology models (35). Notably, HDAC8, which was not susceptible to alkylation by 15d-PGJ 2 -B, has a Leu substituted for Cys at one conserved position and a displaced Cys with a different flanking residue at the other conserved position.…”
Section: Alkylation (Carbonylation) Of Conserved Cysteine Residues Inmentioning
confidence: 91%
“…13,14 However, several factors, including the similarity between their catalytic sites, the difficulty in obtaining purified active proteins and until recently, lack of X-ray crystal structures, have hampered the search for potent isoform-specific inhibitors, and this in turn has slowed down the progress in delineating the biology of the individual HDAC isoforms in cancer. 15,16 Knockdown experiments of selective HDAC isoforms have revealed that HDAC8 is essential for cell survival. 17 HDAC8 is a 49 kDa HDAC isoform with deacetylase activity in vitro that is expressed in multiple tissue types and tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%